Analisis Pengaruh Pertumbuhan Ekonomi, Suku Bunga dan Pengeluaran Pemerintah Terhadap Penerimaan Pajak di Provinsi Papua pada Tahun 2011-2021 - Maria Kristiana; Elsyan R. Marlissa; Yundy Hafizrianda (Universitas Cenderawasih, 2023)
This study aims to analyze the effect of economic growth, interest rates, and government expenditure on tax revenue in Papua Province during the period 2011–2021. The research employs a quantitative approach using multiple linear regression analysis based on secondary data obtained from the Directorate General of Taxes, Statistics Indonesia, and Bank Indonesia. The results show that interest rates have a negative and significant effect on tax revenue, while government expenditure has a positive and significant effect. Meanwhile, economic growth (GRDP) does not have a significant effect on tax revenue. Simultaneously, these variables significantly influence tax revenue with a contribution of 82.4%. These findings indicate that fiscal policy through government expenditure plays an important role in increasing tax revenue, while interest rate stability needs to be maintained to support optimal state revenue. Keywords: economic growth, interest rate, government expenditure, tax revenue